Hypoglycemic effect of Verbesina encelioides (Veterinary Science, 2017)
Human beings and animals, specially canine and feline, are the species in which Diabetes mellitus has been more frequently diagnosed. Due to the need of finding alternative sources of hypoglycemic drugs and in order to get new drugs with this property, the effect of the aqueous extract of heads of Verbesina encelioides (Ve) was studied on glycemia levels in common mice and in transitory hyperglycemic once. In both assays animals were unfed for 15 hours. The different groups of common mice received an oral doses of 2, 3 and 4 g of aqueous extract of Ve per kg weight. After 6 hours glycemia was determined. The control group only received the vehicle. The glycemia levels in animals treated with 2 and 3 g/kg were significantly smaller to those of the control group (P0.01). The 4 g/kg dose was lethal for all mice. The effect of the administration of 2 g Ve per kg weight on mice was evaluated. After 30 minutes, each mouse received an oral dose of 3 g of glucose per kg of weight, to become transitory hyperglycemic mice. The control group only received the vehicle and glucose. Glycemia was determined 1, 2, 3 and 4 hours after glucose was administered. These values were related to the basal glycemia levels. The differences between glycemia and basal values was significantly smaller in the group treated than in the group control (P0.01)
Keywords: Verbesina encelioides; Hypoglycemia